Establishment of Analyzing Method of Fenpropathrin Residue in Angelica dahurica Radix and Osterici Radix - Ham, Hun-Ju; Lee, Byung-gi; Choi, Jeong-Yoon; Ahmed Ishag, Abd Elaziz S.; Hur, Jang-Hyun (Current Traditional Medicine, 2023)
Background: Angelica dahurica Radix and Osterici Radix are perennial herbs belonging to the family Umbelliferae, which are attacked by red spiders; thus, fenpropathrin has been registered to save them from this attack. Fenpropathrin is important in improving the productivity and quality of medicinal herbs due to timely pest control. However, residue may likely remain after harvest, and therefore, the residue analysis is important to ensure pesticides’ safety management. Objective: This study aimed to establish an analysis method for fenpropathrin residues in A. dahurica Radix and O. Radix using GLC-ECD and GC-MS/MS. Methods: Samples were moisturized with distilled water and extracted with acetonitrile. The interferences were removed using SPE cartridges and analyzed by GLC-ECD and GC-MS/MS. Results: Based on pre-experiment results, the analysis method was optimized using the doublecleanup method (SPE-GCB/NH2 and SPE silica cartridges). Fenpropathrin peak was confirmed by GC-MS at the same retention time and with its mass numbers. Nevertheless, the cleanup processes are laborious and require a rather long time. Thus, an additional effortless analysis method was developed using the d-SPE method that can apply to highly selective and sensitive GC-MS/MS techniques. The LOD of GC-ECD and GC-MS/MS was 0.1 and 0.01 ng, respectively. While the LOQ was 0.04 mg/kg for both. Linearity (r2) was > 0.998 (GLC-ECD) and 0.999 (GC-MS/MS). The recoveries at three spiking levels ranged from 83.6-103.1% and 89.6-98.0% for A. dahurica Radix and O. Radix, respectively. Conclusion: The accuracy of the improved method met the standard of the Korean Ministry of Food and Drug Safety. Therefore, the developed methods are expected to be used for analyzing pesticide residues in herbal medicines in Korea and other countries.
Keywords: fenpropathrin